Pragmatic constraints on (adverbial) (temporal) quantification - Percus, Orin (ZAS Papers in Linguistics, 2001)
Even if we can generate a logical form, principles of use may limit the ways in which we can use it. In this paper, I motivate one such principle of use, and explore its effects. Much of the discussion involves kinds of sentences that have received attention in the literature on "individual-level predicates".